2005
DOI: 10.1021/jo0503557
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Cross-Coupling of Imines, Acid Chlorides, and Organostannanes:  A Multicomponent Synthesis of α-Substituted Amides

Abstract: A copper-catalyzed cross-coupling of organotin reagents with imines and acid chlorides is reported. The reaction proceeds efficiently with a range of vinyl-, alkyl-, aryl- and heteroaryl-substituted organostannanes as well as a diverse set of imines of non-enolizable aldehydes. Use of chloroformates also allows for the formation of N-protected alpha-substituted amines. This chemistry has been applied to the synthesis of isoquinoline alkaloid derivatives through the activation of cyclic imines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 57 publications
(29 reference statements)
2
12
0
Order By: Relevance
“…While several common Lewis acids (TiCl 4 , AlCl 3 , CeCl 3 and BF 3 ·Et 2 O) were trialled unsuccessfully, a different strategy based on the formation of solid bonds indicated that carbonyl derivatives such as acetyl chloride or methyl chloroformate were, in contrast, efficient activators of the C=N double bond, albeit used in stoichiometric amounts. This result is consistent with some previous studies reporting the activation of imines under an acyliminium form and the subsequent addition of either aromatic [1723 26–27] or non-aromatic [3435] organometallic nucleophiles onto carbon.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…While several common Lewis acids (TiCl 4 , AlCl 3 , CeCl 3 and BF 3 ·Et 2 O) were trialled unsuccessfully, a different strategy based on the formation of solid bonds indicated that carbonyl derivatives such as acetyl chloride or methyl chloroformate were, in contrast, efficient activators of the C=N double bond, albeit used in stoichiometric amounts. This result is consistent with some previous studies reporting the activation of imines under an acyliminium form and the subsequent addition of either aromatic [1723 26–27] or non-aromatic [3435] organometallic nucleophiles onto carbon.…”
Section: Resultssupporting
confidence: 93%
“…However, an increased range of aromatic moieties can be introduced through the use of organometallic compounds. The most commonly employed reagents are organoindium [1718], organolithium [1920], organomagnesium [2122], organotin [23], or organozinc compounds [24–25]. However, although these are recognized as mild multi-purpose reagents, sole examples of their use in nucleophilic additions on acylimium salts consist, to the best of our knowledge, of the phenylation of quinolinium salts using diphenylzinc [26–27].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the presence of the amine group and the choice of pH of the elution phase for HPLC leads to a retention of an impurity, the nature of which could not be elucidated from 1 H and 13 C NMR analyses. As anticipated based on our prior work, 5 electron deficient aldehydes 1 { 4 } and 1 { 7 } afforded the indenoisoquinoline products 6 { 4, 1, 1-3 } and 6 { 7, 1, 1-3 } in diminished yields lower than 30% (mostly 7-15%) and somewhat lower purities (88-94%).…”
Section: Resultssupporting
confidence: 72%
“…Copper catalyzed a coupling of imines, acid chlorides and organotin reagents (Eq. (177)) [934]. Copper catalyzed the addition of arylboronic acids to azodicarboxylates forming aryl-substituted hydrazines [935].…”
Section: Formation Of Carbon-carbon and -Nitrogen Bonds From Carbonylmentioning
confidence: 99%